A New Method of Airway Management in Patients Undergoing Gasserian Ganglion Thermal Coagulation: Preliminary Results. Issue 3 (July 2015) - Klug, Wolfgang; Reiterer, Christian; Bukaty, Adam; Schramm, Wolfgang
Abstract : Background: Airway management in patients undergoing neurosurgical interventions for trigeminal neuralgia can often prove difficult. This is because the patient's assistance is required during this neurosurgical intervention, and moreover, the site of puncture lies within the working area of the anesthesiologists. An obvious alternative for airway management is the use of a nasopharyngeally placed tube. The purpose of the present study was to objectify the gas exchange in patients during this new ventilation technique. Methods: In 5 patients, a tube with a 5 mm internal diameter was placed nasopharyngeally after induction of general anesthesia and ventilation was then manually assisted. The intraoperative partial pressure values of CO2 (pvCO2 ) and O2 (pvO2 ) in the venous blood were then compared with their respective patient's preoperative baseline pvCO2 and pvO2 levels. Blood pressure, heart rate, and SpO2 were continuously and noninvasively monitored. During the entire surgical intervention, patients were ventilated with a fraction of inspired oxygen (FiO2 ) of 1.0 and a fresh gas flow of 18 L per minute. Results: All patients exhibited sufficient oxygenation during the entire procedure under manual ventilation. There were no excessive deviations in pvCO2 from baseline levels. Furthermore, no incidents of hemodynamic instability occurred. Mean duration of the neurosurgical procedure was 54 minutes. Impairment of intraoperative verbal communication was not observed with the nasopharyngeal tube in situ. Conclusions: This preliminary study suggests that manually assisted ventilation with pure oxygen using a nasopharyngeally placed tube seems to be a sufficient airway management technique during thermal coagulation of the Gasserian ganglion.